Transformative Education and Experience-Based Learning for Refugee Empowerment and Peaceful Coexistence in European Society: Role-Playing and Drama Simulation Approaches - Kanatelia, Eleftheria (Epistēmēs Metron Logos, 2023)
This essay underscores the significance of transformative education and experience-based learning methods. In "The Path" workshop, refugees and European citizens actively engage, sharing transformative experiences through role-playing and drama simulation. These methods serve as a powerful catalyst for social change by fostering empathy, cross-cultural understanding, and harmonious coexistence. By immersing participants in these learning experiences, the transformative potential of this educational approach becomes evident, contributing to a more informed, inclusive, and empathetic European society.